Effects of forced taxonomic transitions on metabolic composition and function in microbial microcosms. Issue 5 (3rd August 2020) - Louca, Stilianos; Rubin, Ilan N.; Madilao, Lufiani L.; Bohlmann, Jörg; Doebeli, Michael; Wegener Parfrey, Laura
Summary: Surveys of microbial systems indicate that in many situations taxonomy and function may constitute largely independent ('decoupled') axes of variation. However, this decoupling is rarely explicitly tested experimentally, partly because it is hard to directly induce taxonomic variation without affecting functional composition. Here we experimentally evaluate this paradigm using microcosms resembling lake sediments and subjected to two different levels of salinity (0 and 19) and otherwise similar environmental conditions. We used DNA sequencing for taxonomic and functional profiling of bacteria and archaea and physicochemical measurements to monitor metabolic function, over 13 months. We found that the taxonomic composition of the saline systems gradually but strongly diverged from the fresh systems. In contrast, the metabolic composition (in terms of proportions of various genes) remained nearly identical across treatments and over time. Oxygen consumption rates and methane concentrations were substantially lower in the saline treatment, however, their similarity either increased (for oxygen) or did not change significantly (for methane) between the first and last sampling time, indicating that the lower metabolic activity in the saline treatments was directly and immediately caused by salinity rather than the gradual taxonomic divergence. Our experiment demonstrates that strong taxonomic shifts need not directly affect metabolic rates.